Understanding the WTO Sanitary and Phytosanitary Agreement - Edward A. Evans (EDIS, 2004)
This publication is part of the Understanding Trade Policy Issues series. International trade liberalization and the general globalization of the world economy over the past two decades has meant that growers, businesses, and community groups must become familiar with trade polices and their terminologies to reap the benefits of globalization and to minimize costs. Consequently, the aim of this series is to help people understand the issues involving the benefits and problems associated with global trade. This publication, the first of the series, discusses the term “WTO-SPS Agreement” (the Sanitary and Phytosanitary Agreement under the World Trade Organization). This is EDIS document FE492, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published August 2004.